ANALISIS RISIKO DALAM MENINGKATKAN PENDAPATAN USAHA PADA UMKM KERUPUK KEMPLANG DARWATI DESA BAYUNG LENCIR SUMATERA SELATAN - Desi Oktariyanti (Program Studi Manajemen Keuangan Syariah, 2021)
The essay is to disclose what the risks ae in darmanto blooms, how the income is going to be in the darwati bar. To achieve that goal, the thesis employed utilized a subjective methodology utilizing a spellbinding technique aimed at obtaining information about certain conditions and explaining and describing the research done in the examination climate, the subjective methodology was that the student was to seek literature or research related theories first, then it was adapted to a field of research. The method used in this study is by data collection techniques: observation, interview, and documentation with this methodology, it is acquired. The results showed that accompanying exploration: the risks of production, price risk, financial risk, market and market risk. The net profit of the company‟s belatoned crackers was 3,586,000 - 7,290,000 . The income from the bell-to-wall, bell-to-wall business, often goes up and down depending on market demand. A way to increase income in darwati‟s hatchling chips is to weight the risk involved and plan them before they come. Among other ways to increase income in financial management at the bank of wwii in the early days of the season, pricing solutions suggest that the price of these crackers wa significant during the celebration of the seasons, and when the scarcity of production of these would result in reduced the size of the crackers from the norm, financial risk solutions show that existing finance in banks and other loans must match the return, market and marketing risk solutions by creating products that are hyginies and applying production products to be tested and maximize products with different characteristics.